Students’ preferences for learning English literature: balancing physical and virtual instruction post-pandemic / Dr. Jamiah Baba ... [et al.] - Baba, Jamiah; Mohd Shahrom, Syahreena; Mohd Izam, Munirah; Abdul Hamid, Mohd Hafriz (Universiti Teknologi MARA, Kedah, 2025)
Higher learning has undergone dramatic changes due to the COVID-19 where learners have to move from teaching and learning in person to online learning. With educational institutions transitioning to a blend of in-person and online learning after the pandemic, understanding students' preferred methods for learning English literature is now crucial. This study explores students’ preferences in learning English literature in terms of the physical classroom, the virtual, or a combination of the two in a post-pandemic context. It analyses the advantages and disadvantages brought by each type of instruction and how efficient they are, as well as how efficient are hybrid models as far as both types of instruction are concerned. The findings of the study show that even if students appreciate the ease and availability of resources provided by virtual learning, they still appreciate the interactive and social features of physical classrooms. It seems that if hybridisation of the in-classroom and the online environments is applied, students’ needs are best met. The findings suggest that a balanced approach, incorporating both in-person and online components, can enhance students’ learning experience and address the diverse preferences of students in a post-pandemic educational landscape.